2019
DOI: 10.1093/mnras/stz2760
|View full text |Cite
|
Sign up to set email alerts
|

Particle transport in hybrid PIC shock simulations: A comparison of diagnostics

Abstract: Recent in-situ and remote observations suggest that the transport regime associated with shock accelerated particles may be anomalous i.e., the Mean Square Displacement (MSD) of such particles scales non-linearly with time. We use self-consistent, hybrid PIC plasma simulations to simulate a quasi-parallel shock with parameters compatible with heliospheric shocks, and gain insights about the particle transport in such a system. For suprathermal particles interacting with the shock we compute the MSD separately … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Particle-in cell (PIC) simulations show these variations (e.g. Trotta et al 2020) and small-scale variations have been observed in interplanetary shocks by the Cluster spacecraft (e.g. ).…”
Section: Compound Seed Particlesmentioning
confidence: 89%
“…Particle-in cell (PIC) simulations show these variations (e.g. Trotta et al 2020) and small-scale variations have been observed in interplanetary shocks by the Cluster spacecraft (e.g. ).…”
Section: Compound Seed Particlesmentioning
confidence: 89%
“…For instance, shock-reflected particles may show superdiffusive behavior (e.g., ref. 53), and coherent structures present in the up-/downstream of the shock provide excellent traps (or accelerators) for energetic particles (40).…”
Section: Physicsmentioning
confidence: 99%
“…Particle-in cell (PIC) simulations show these variations (e.g. Trotta et al 2020) and small-scale variations have been observed in interplanetary shocks by the Cluster spacecraft (e.g. Kajdič et al 2019).…”
Section: 8mentioning
confidence: 92%